Integrative Analysis Revealed Stemness Features and a Novel Stemness-Related Classification in Colorectal Cancer Patients - Ye, Meng-Ling; Li, Si-Qi; Yin, Yi-Xin; Li, Ke-Zhi; Li, Ji-Lin; Hu, Bang-Li (Frontiers in Cell and Developmental Biology, 2022)
Cancer stem cells play crucial roles in colorectal cancer (CRC) tumorigenesis and treatment response. This study aimed to determine the value of the mRNA stemness index (mRNAsi) in CRC and introduce a stemness-related classification to predict the prognosis of patients. The mRNAsi scores and RNA sequence data of patients with CRC were analysis. We found that, high mRNAsi scores were related to early-stage CRC and a better patient prognosis. Two stemness-based subtypes (subtype I and subtype II) were identified, and patients in subtype I presented a significantly better prognosis than did those in subtype II. Patients in these two subtype groups presented significantly different tumor immunity scores and immune cell infiltration patterns. Genomic variations revealed that patients in subtype I had a lower tumor mutation burden than those in subtype II. A three-gene stemness subtype predictor was established, which showed good diagnostic value in discriminating patients in the different subtypes. A prognostic signature based on five stemness-related genes was constructed and validated in two independent cohorts and clinical samples, showing a better prognostic performance than other clinical parameters. We concluded that mRNAsi scores were associated with the clinical outcome in CRC patients. The stemness-related classification was a promising prognostic predictor for CRC patients.